Estimating the Economic and Distributional Impacts of the Regional Comprehensive Economic Partnership - Estrades Pineyrua, Carmen; Maliszewska, Maryla; Osorio-Rodarte, Israel; Seara E Pereira, Maria Filipa (Washington, DC: World Bank, 2022)
This paper applies a top-down, macro-micro modeling framework that links a computable general equilibrium model with the survey-based global income distribution dynamics model to assess the economic and distributional effects of the implementation of the Regional Comprehensive Economic Partnership (RCEP). Reductions of tariffs and non-tariff measures, implementation of a rule of origin, together with productivity gains stemming from trade cost reductions can strengthen regional trade and value chains among Regional Comprehensive Economic Partnership members. The results of the analysis indicate that in an already deeply integrated region, tariff liberalization alone brings little benefit, with estimated real income gains of 0.21 percent relative to the baseline (without the RCEP) in 2035. With liberal rules of origin, the gains in real income could double to 0.49 percent. The biggest benefits accrue when the productivity gains are considered, increasing real income by as much as 2.5 percent for the trade bloc. In this scenario, trade among RCEP members increases by 12.3 percent in 2035 relative to the baseline. The RCEP also has the potential to lift 27 million additional people to middle-class status by 2035. It will also boost wages, with faster gains in sectors that employ larger shares of women. The aggregate effects mask large variety of outcomes across countries, with Vietnam expected to register the highest trade and income gains. Implementation of the RCEP help partially mitigate the negative economic impacts of COVID-19 in the East Asia and the Pacific region.